PSYCHOLOGICAL ASPECTS OF STUDENT ADAPTATION TO A NEW LEARNING ENVIRONMENT - Ibragimova Dilnoza Xayrullo qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Adaptation of students to study in higher education is a topical issue of our time, because the professional activity and personal development of the future specialist depends on the success of the adaptation process. Many modern students face difficulties in self-development. To solve this problem, it is important to study the adaptation of students to the educational process based on practical and theoretical knowledge. Such adaptation helps to overcome psychological barriers.